Forms and meanings of intensification: a multifactorial comparison of quite and rather - Guillaume Desagulier (Anglophonia)
To capture usage-based relations between near-synonyms, I cluster collocation data using exploratory multifactorial methods. My investigation is restricted to quite and rather in the contexts where they intensify adjectives in the British National Corpus. I use correspondence analysis and multiple correspondence analysis to visualize and interpret distances between (a) the two intensifiers, (b) the adjectives they modify and the respective semantic classes they belong to, and (c) syntactic information regarding how intensifiers and adjectives pattern together. Results show that quite and rather constructions form a consistent network. The first key finding is that they typically follow a division of labor in the intensification of adjectival meanings. When a positive and a negative connotation are available for a given adjective, rather tends to intensify the negatively connoted adjective. The second key finding is the following: in the strict frame of the pre-determiner vs. pre-adjectival alternation, quite displays a preference for the pre-determiner position, and rather for the pre-adjectival position.